2015
DOI: 10.1007/s10571-015-0301-8
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of IRF6 Attenuates Hydrogen Dioxide-Induced Oxidative Stress via Inhibiting Mitochondrial Dysfunction in HT22 Cells

Abstract: Oxidative stress-induced cell damage is involved in many neurological diseases. Interferon regulatory factor 6 (IRF6), a member of the IRF family of transcription factors, is required for the differentiation of skin, breast epithelium, and oral epithelium. However, the regulation and function of IRF6 in central nervous system remain unknown. This study aimed to investigate the role of IRF6 in hydrogen peroxide (H2O2)-induced oxidative neuronal injury in HT22 mouse hippocampal cells. Treatment with H2O2 signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…At the same time, mitochondrial dysfunction promotes abnormalities in the mitochondrial respiratory chain’s electron transport pathways, ultimately interfering with the intracellular ATP production [5,32]. Consistent with previous studies [33,34,35], current studies have shown that when cells are exposed to H 2 O 2 , the MMP levels and ATP content are significantly reduced compared to controls, whereas the co-treatment with glutathione significantly reverses the H 2 O 2 -induced loss of MMP and APT. However, in the presence of ZnPP, the glutathione-mediated repair of the mitochondrial dysfunction and decreased production of ATP were significantly diminished.…”
Section: Discussionsupporting
confidence: 88%
“…At the same time, mitochondrial dysfunction promotes abnormalities in the mitochondrial respiratory chain’s electron transport pathways, ultimately interfering with the intracellular ATP production [5,32]. Consistent with previous studies [33,34,35], current studies have shown that when cells are exposed to H 2 O 2 , the MMP levels and ATP content are significantly reduced compared to controls, whereas the co-treatment with glutathione significantly reverses the H 2 O 2 -induced loss of MMP and APT. However, in the presence of ZnPP, the glutathione-mediated repair of the mitochondrial dysfunction and decreased production of ATP were significantly diminished.…”
Section: Discussionsupporting
confidence: 88%
“…However, HO-1 activation is recognized as a cell protection mechanism against oxidative stress-mediated mitochondrial dysfunction through inactivation of the mitochondria-mediated intrinsic apoptosis pathway [26,27]. Consistent with previous studies [38,39,40], the present study shows that when cells were exposed to H 2 O 2 , MMP levels and ATP contents were significantly reduced compared to controls, whereas PG significantly reversed the H 2 O 2 -induced loss of MMP and APT. However, in the presence of ZnPP, PG-mediated repair of mitochondrial dysfunction and the decreased production of ATP were significantly abolished.…”
Section: Discussionsupporting
confidence: 87%
“…ZBTB20 is also highly expressed uniquely in SEGAs, and is a transcriptional repressor with roles in neurogenesis, glucose homeostasis, and postnatal growth [48]. IRF6 (Interferon regulatory factor 6) plays a role in regulating mammary epithelial cell proliferation, while specifically expressed in SEGAs in comparison to other brain tumors but is expressed in other cancers and normal tissues [49]. These top genes have been reported to be epigenetically regulated bearing histone modifications: H3K27 trimethylation (H3K27me3) mark in brain for HMX2, HMX3, IRF6; H3K4me2 and H3K27me3 in neural precursor cells (NPC) for HMX2, HMX3, and VAX1 [50].…”
Section: Discussionmentioning
confidence: 99%